(untitled) (The Pakistan Development Review, 2025)
During the past decade every year the Punjab government has faced an awkward situation at wheat harvest. It must buy millions of tons of wheat at an above-market price despite massive carry-forward stocks already lying in its granaries. Cost of procuring such huge quantities and subsidising sales to flour mills is enormous and is met with commercial borrowing. In recent years, the government has struggled to balance its accounts for wheat operations; its outstanding liability to commercial banks stood at Rs. 444.7 billion in June 2018, viz. 22 percent of the total budget of the province in 2017-18. Clearly, the government procures more wheat annually than it needs with borrowed money that it cannot pay back. Ostensibly, wheat procurement aims to benefit small farmers, but its procedures exclude, rather than include them. Conversely, consumers end up buying expensive wheat-flour. A significant beneficiary of the procurement regime appears to be commercial banks finance the procurement and earn interest thereupon. Keywords: Food Subsidy, Wheat Procurement, Subsidy Reform